Moto-mechanization in the irrigated valley of San Francisco River: case study of Project Bebedouro - Lal, Harbans (Pesquisa Agropecuaria Brasileira, 2014)
The paper evaluates the intensity and mode of utilization of tractors in the Project Bebedouro of CODEVASF, based on the data supplied by CAMPIB (Cooperativa Agrícola Mista do Projeto de Irrigação de Bebedouro Ltda.) of the region. Three years data of 15 tractors in case of CAMPIB and two years of one tractor in case of Fazenda Delta Agropecuária Ltda. have been analysed. The tractors in the project vicinity are primarily utilized for land preparation operations (plowing and harrowing) varying in range of 70% to 80% of productive hours in case of CAMPIB and 58% of total hours in case of Delta, with the annual use of 1000-1400 hours in both cases. The other operations carried out with tractors are transportation, threshing and land levelling by CAMPIB and transportation and application of calcium powder and chemical fertilizers in case of Delta. The mean annual use of working days of CAMPIB tractors varies from 117 to 141 days with monthly working days use of 9.7 to 11.8 days per trator. In the project, apart from tractors, the animal power is used principally of ridging operation and covering fertilizer after manual application. Rest all the operations are done manually. The cost of tractor operations varies from 15% to 46% of total cost of mechanization depending on the type of crop, with mean operational capacities: 0.31 ha/hr (plowing), 0.58 ha/hr (harrowing), 0.55 ha/hr (ridging), 11.7 days (60 kg)/ha (threshing), 0.55 ha/hr (chopping) and 0.15 ha/hr (land leveling).